Reflowable documents composed from pre-rendered atomic components - Pinkney, Alexander J.; Bagley, Steven R.; Brailsford, David F. (2011)
Mobile eBook readers are now commonplace in today’s society, but their document layout algorithms remain basic, largely due to constraints imposed by short battery life. At present, with any eBook file format not based on PDF, the layout of the document, as it appears to the end user, is at the mercy of hidden reformatting and reflow algorithms interacting with the screen parameters of the device on which the document is rendered. Very little control is provided to the publisher or author, beyond some basic formatting options. This paper describes a method of producing well-typeset, scalable, document layouts by embedding several pre-rendered versions of a document within one file, thus enabling many computationally expensive steps (e.g. hyphenation and line-breaking) to be carried out at document compilation time, rather than at ‘view time’. This system has the advantage that end users are not constrained to a single, arbitrarily chosen view of the document, nor are they subjected to reading a poorly typeset version rendered on the fly. Instead, the device can choose a layout appropriate to its screen size and the end user’s choice of zoom level, and the author and publisher can have fine-grained control over all layouts.